Rational Proteomic Analysis of a New Domesticated Klebsiella pneumoniae x546 Producing 1,3-Propanediol - Wang, Xin; Zhang, Lin; Chen, Hong; Wang, Pan; Yin, Ying; Jin, Jiaqi; Xu, Jianwei; Wen, Jianping (Frontiers in Microbiology, 2021)
In order to improve the capability of Klebsiella pneumoniae to produce an important chemical raw material, 1,3-propanediol (1,3-PDO), a new type of K. pneumoniae x546 was obtained by glycerol acclimation and subsequently was used to produce1,3-PDO. The original strain yielded 45.91 g/L 1,3-PDO, while K. pneumoniae x546 produced 1.51-fold 1,3-PDO (69.35 g/L) when Na+ pH neutralizer was used to control the pH value during fermentation in a 7.5 L fermentor. After the addition of betaine for 24 h, the yield of 1,3-PDO reached up to 74.44 g/L, which was 40% shorter than the original fermentation time of 40 h. In order to study the potential mechanism of the production improvement of 1,3-PDO, the Tandem Mass Tags (TMT) was applied to investigate the production of 1,3-PDO in K. pneumoniae. Compared with the control group, 172 up-regulated proteins and 293 down regulated proteins were identified. Through GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway analysis, it was found that some proteins (such as ThrB, PurT, PurC, etc.) involved in the fermentation process, while some other proteins (such as ProX, ProW, ProV, etc) played a significant role after the addition of betaine. Moreover, combined with the metabolic pathway of K. pneumoniae producing 1,3-PDO, the proteins that had an effect on the process (such as DhaB, DhaT, DhaD, DhaK, etc.) were analyzed. The process of producing 1,3-PDO in K. pneumoniae was explained from the perspective of TMT for the first time, which provided a theoretical basis for which genes might need to be modified to improve the yield of 1,3-PDO. Due to the use of Na+ pH neutralizer in the fermentation, the subsequent environmental pollution treatment cost is greatly reduced, showing high potential for industry application in the future.